Mathematical Students’ Satisfaction with Semester and Annual Service Quality - Badaila, Bishnu Bahadur (Journal of Mathematics Education, 2026)
This study examines the satisfaction of Master’s level students in Mathematics Education with the quality of services offered by Tribhuvan University in Nepal. It looks several dimensions of service quality including academic and non-academic aspects, course design, delivery and assessment, group size, program issues, reputation, and access. The study adopts a survey-based approach to investigate the relationship between these service quality dimensions and students’ overall satisfaction, as well as differences in satisfaction levels based on gender, age groups, and academic systems (semester vs. annual). A total of 60 students participated in the study, equally divided between the semester and annual systems. Data were collected using a 5-point Likert scale questionnaire and analyzed through regression analysis, z-test, frequency, percentage, mean, and standard deviation. The results reveal strong relationship between factors affecting service quality and students’ general satisfaction. However, the findings indicate no significant difference in the satisfaction levels between students enrolled in the semester system and those in the annual system. Hence both groups perceived the quality of services provided by Tribhuvan University to be comparable.